Professional Development for the Early Care and Education Workforce in Shelby County, Tennessee - Cannon, Jill S. (RAND Corporation, 2016)
The early care and education caregivers with whom children interact can play an important role in the children's cognitive, social, and emotional development. This report examines how caregivers with licensed providers in Shelby County, Tennessee, gain relevant knowledge and skills, specifically through ongoing professional development opportunities, for working with infants, toddlers, and preschool-age children.